1986
DOI: 10.1097/00004630-198607000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Injuries Among 87,000 Massachusetts Children and Adolescents: Results of the 1980-81 Statewide Childhood Injury Prevention Program Surveillance System

Abstract: This study describes the incidence of fatal and nonfatal injuries occurring in 87,022 Massachusetts children and adolescents during a one-year period. A surveillance system for injuries at 23 hospitals captured 93 per cent of all discharges for ages 0-19 in the 14 communities under study. Sample data were collected on emergency room visits, hospital admissions, and deaths for all but a few causes of unintentional injuries. The overall incidence was 2,239 per 10,000. The true incidence rates are probably higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 0 publications
4
64
1
Order By: Relevance
“…The data from the present study demonstrates that males are more likely than females to suffer a Crotaline snakebite that is subsequently treated with antivenom (2.1:1). This finding is consistent with previous studies of overall injury ratios and studies of snakebites where the male:female snakebite ratio has ranged from 1.4:1 to 2.8:1 [3,[5][6][7][8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data from the present study demonstrates that males are more likely than females to suffer a Crotaline snakebite that is subsequently treated with antivenom (2.1:1). This finding is consistent with previous studies of overall injury ratios and studies of snakebites where the male:female snakebite ratio has ranged from 1.4:1 to 2.8:1 [3,[5][6][7][8].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in studies of pediatric injury rates, males are injured more commonly. A study of 87,000 Massachusetts children and adolescents demonstrated a male:female injury ratio of 1.66:1 [3]. While the etiologies of this difference are likely multifactorial, sex-specific differences in risk-taking behaviors have been implicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] In infants and toddlers, physical abuse is the cause of 12% to 20% of fractures. 9 Although unintentional fractures are much more common than fractures caused by child abuse, the physician needs to remain aware of the possibility of inflicted injury.…”
Section: Differential Diagnosis Of Fractures Trauma: Child Abuse Versmentioning
confidence: 99%
“…1 A study of injury incidence over a one-year period in Massachusetts found that 96% of injuries in children did not result in death; the child was treated and released from an emergency department (ED). 4 More than half of emergency visits for children ages 5-14 years are for injury, and injuries account for more than 11 million emergency visits each year by U.S. children. [5][6][7] The home has been implicated as a leading location of injury for U.S. children.…”
mentioning
confidence: 99%